2018
DOI: 10.5194/tc-2018-53
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A constraint upon the basal water distribution and basal thermal state of the Greenland Ice Sheet from radar bed-echoes

Abstract: Abstract. There is widespread, but often indirect, evidence that a significant fraction of the bed beneath the Greenland Ice Sheet is thawed (at or above the pressure melting point for ice). This includes the beds of major outlet glaciers and their tributaries and a large area around the North-GRIP borehole in the ice-sheet interior. The ice-sheet scale distribution of basal water is, however, poorly constrained by existing observations. In principle, airborne radio-echo sounding (RES) en-5 ables the detection… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 23 publications
3
36
0
Order By: Relevance
“…The latter of these mechanisms, initiated either by velocity changes within the ice column or in basal thermal state, would give rise to large‐scale folding and deformation like that seen here (Weertman, ; Wolovick et al, ). While it has been noted that some UDRs in Greenland do not have a clear relationship to known basal water networks (Wolovick et al, ), the distribution of observed features is consistent with radar basal water predictions (Chu et al, ; Jordan et al, ). Additionally, these are within a region of elevated geothermal heat flux (>58 mW/m 2 ; Martos et al, ; Figure b), and transitional basal thermal state (Chu et al, ; MacGregor et al, ).…”
Section: Interpreting Surface Expressionssupporting
confidence: 73%
See 4 more Smart Citations
“…The latter of these mechanisms, initiated either by velocity changes within the ice column or in basal thermal state, would give rise to large‐scale folding and deformation like that seen here (Weertman, ; Wolovick et al, ). While it has been noted that some UDRs in Greenland do not have a clear relationship to known basal water networks (Wolovick et al, ), the distribution of observed features is consistent with radar basal water predictions (Chu et al, ; Jordan et al, ). Additionally, these are within a region of elevated geothermal heat flux (>58 mW/m 2 ; Martos et al, ; Figure b), and transitional basal thermal state (Chu et al, ; MacGregor et al, ).…”
Section: Interpreting Surface Expressionssupporting
confidence: 73%
“…Various geometric features, including lineations, troughs, and peaks, are visible in the RSE (Movie S1). Interpretation of these features is facilitated by the comparison with BM3, (Morlighem et al, ) and along‐track radargrams from National Aeronautics and Space Administration's Operation IceBridge (Rodriguez‐Morales et al, ; Figure a), as well as with complementary data sets (Figure ), including interferometric synthetic aperture radar‐derived surface ice velocity (Joughin et al, ), radar‐derived basal water (Jordan et al, ), and magnetic‐derived geothermal heat flux (Martos et al, ). On initial comparison to BM3, the RSE (Figure b) replicates fundamental landscape features.…”
Section: Interpreting Surface Expressionsmentioning
confidence: 99%
See 3 more Smart Citations